2018
DOI: 10.1109/tcomm.2018.2835479
|View full text |Cite
|
Sign up to set email alerts
|

Caching With Time-Varying Popularity Profiles: A Learning-Theoretic Perspective

Abstract: Content caching at the small-cell base stations (sBSs) in a heterogeneous wireless network is considered. A cost function is proposed that captures the backhaul link load called the "offloading loss", which measures the fraction of the requested files that are not available in the sBS caches.As opposed to the previous approaches that consider time-invariant and perfectly known popularity profile, caching with non-stationary and statistically dependent popularity profiles (assumed unknown, and hence, estimated)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 34 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…In [32], a reinforcement learning framework was proposed while considering popularity dynamics into the analysis in order to refresh the caches in BSs and to minimize delivery cost. In [33], the loss due to outdated caching policy was analyzed for a small cell BS and an updating algorithm to minimize the offloading loss was proposed. Based on real-data observations, [34] established a workload model and then developed simple caching content replacement policies for edge-caching networks.…”
Section: A Related Literature Reviewmentioning
confidence: 99%
“…In [32], a reinforcement learning framework was proposed while considering popularity dynamics into the analysis in order to refresh the caches in BSs and to minimize delivery cost. In [33], the loss due to outdated caching policy was analyzed for a small cell BS and an updating algorithm to minimize the offloading loss was proposed. Based on real-data observations, [34] established a workload model and then developed simple caching content replacement policies for edge-caching networks.…”
Section: A Related Literature Reviewmentioning
confidence: 99%
“…Proof: Suppose the number of users arriving in a unit of time may be 0, 1, 2, 3 • • • . The number of requests across users in any interval follows an independent Homogeneous Poisson distribution [28] and then we can record the arrival rate of users as λ in following the Homogeneous Poisson distribution. Thus, the probability that the k in users reach the BS coverage within the time interval t can be expressed as…”
Section: The Probability Of Files Being Requestedmentioning
confidence: 99%
“…The authors of [26] observed that most graphics density changes over time with the number of edges growing superlinearly in the number of nodes and the average distance between nodes often shrinking over time. In [27], [28], they found that in many applications, the popularity profile is unknown and changes over time; hence, they analyzed the cache with nonstationary and statistically dependent popularity profiles (hypothetically unknown and therefore estimated) from a learning theory perspective. Liu et al [29], [30] proposed a novel evolving model in which the hybrid interactions among entities, based on whether they belong to the same type, are classified into intertype and intratype interactions that are characterized by two joint graphs evolving over time.…”
Section: Introductionmentioning
confidence: 99%
“…To bypass this bottleneck, we note that the cost function in (3) is linear and the transition probabilities of a content does not affect the others. Hence, we can separate the value function in (7) into N independent value functions each representing a distinct content. For each content n, we have…”
Section: Mdp Formulationmentioning
confidence: 99%
“…In [6], this approach has been extended to a cooperative caching framework, where the SBSs fetch a requested content from neighboring SBSs if it is cached there. In [5], a cache replacement strategy has been introduced for time-varying popularity scenario to maximize the local service rate with a minimum replacement cost, while a more theoretical approach is taken in [7], which studies the cache update policy in the case of time-varying content popularities.…”
Section: Introductionmentioning
confidence: 99%